Habitat suitability as an indicator of urbanisation potential in four UK mammals - Fung,YY; Carbone,C; Scott-Gatty,K; Freeman,R; Ewers,RM; Turner,J (Mammal Review, 2024)
1. Urban environments provide opportunities for some species but are inhospitable for others. However, those which thrive can be found at higher densities in human-dominated landscapes than in more rural habitats. This highlights the importance of understanding species responses to human environments. It is not only important for the conservation of urban wildlife but also may provide fundamental insights into human-wildlife coexistence globally.2. Here, we use citizen science data to predict the habitat suitability of Greater London for the West European hedgehog (Erinaceus europaeus), the red fox (Vulpes vulpes), the European badger (Meles meles) and the Eastern grey squirrel (Sciurus carolinensis).3. Results indicate that the four target species prefer different urban habitats, indicating different levels of urbanisation potential. Foxes and grey squirrels are able to thrive in inner urban areas, with the highest values of habitat suitability for these species found in central London, whereas for hedgehogs and badgers, the highest habitat suitability occurs in suburban and more rural habitats in outer London, respectively.4. These results highlight a gradient in urban tolerance, from squirrels and foxes to hedgehogs and badgers. This work also shows the importance of urban green spaces as habitats for wildlife.